Tetrahedron diagram in Chern-Simons-witten theory - Zen, Freddy Permana; Kosasih, Jusak Sali; Zainuddin, Hishamuddin; Wardayaa, A. Y. (2005)
Extended Wilson loop operators, in particular tetrahedron operator is discussed in (2+1)-dimensional Chern-Simons theory. This operator emerges from the contribution terms in two-particle scattering amplitude. For gauge group SU(N) and specific choices of representation, we evaluate this diagram exactly in terms of the vacuum expectation values of Wilson loop operators.